Moral injury and well-being in essential workers during the COVID-19 pandemic: local survey findings. Issue 3 (12th January 2022) - Guy, Catherine; Kunonga, Edward; Kennedy, Angela; Patel, Paras
Abstract : Background: Essential workers have faced many difficult situations working during the pandemic. Staff may feel that they, or other people, have acted wrongly and be distressed by this. This represents moral injury, which has been linked with significant mental ill health. Methods: This survey asked essential workers in County Durham and Darlington about their experiences during the first wave of the pandemic and anything they felt would help. Well-being and moral injury were rated using sliders. Results: There were 566 responses. A majority of respondents reported feeling troubled by other people's actions they felt were wrong (60% scored over 40, where 0 is 'not at all troubled' and 100 'very troubled', median score=52.5). Respondents were generally less troubled by their own actions (median score=3). Well-being and moral injury scores varied by employment sector (eg, National Health Service (NHS) staff were more troubled by the actions of others than non-NHS staff). Staff suggestions included regular supervisor check-ins, ensuring kindness from everyone, fair rules and enforcement and improving communication and processes. Respondents offered simple, practical actions that could be taken by leaders at team, organisation, societal and governmental levels to tackle moral injury and the underlying causes of moral injurious environments. Conclusion: Using these findings to develop a strategy to address moral injury is important, not only for staff well-being, but staff retention and continued delivery of vital services in these challenging times. Working together, we can seek to reduce and mitigate 'moral injury' the same way we do for other physical workplace 'injuries'.